Alignment of Digital Strategies in a South African Group of Information Communication Technology Companies - Roux, Gerhard (My University, 2019)
ABSTRACT Digital Business Strategy is a necessary and strategic response to ensure relevance and competitiveness of all organisations during the fourth industrial revolution. Through the digitalisation of physical systems, organisations are required to evolve and meet the demands of a changing customer dynamic and technological landscape. Digital transformation has been shown to increase competitiveness and profitability of organisations whose leadership has been transformational to the opportunities brought through digitalisation. It was thus the objective of this report to establish the alignment of the respective digital business strategies of a group of related ICT service providers against that of the group holding company, and their use of digital technologies for the achievement thereof. This report was conducted through an exploratory qualitative study where data was gathered through semi structured interviews with managing executives of the respective holding and operating companies. Through the use of thematic analysis, the executives’ respective strategy formulation and execution was reviewed to establish if and how they are leveraging digital technologies for the benefit of customers, employees and shareholders alike in line with industry trends. Digital business strategy was found to be a distinct strategic choice considering both internal digital transformation and external customer specific digital transformations. The digital business strategies uncovered sought to deploy technology for the betterment of operational processes to save costs, optimise and scale, whilst increasing customer choice and experience. The lack of a clear and universal definition of a digital business strategy along with the limited use of frameworks, methodologies and tools was also identified within the organisation. Although all operating companies meaningfully contributed to the combined strategy, the development of standardised models and tools could significantly assist the group with greater focus and ultimate alignment toward group objectives. The requirement of an ICT provider is clear and simple: Be digitally transformed internally, whilst leveraging digital technology to deliver value for customers and partners alike though products, services and technology solutions to their respective business problems. This paper contributes to the body of knowledge through having a clearer understanding of digital business strategy within a group of diversified ICT providers in South Africa.
Keywords: Keywords: Digital Business Strategy; Digital Transformation; Fourth Industrial Revolution; ICT Provider